Serine racemase deletion alters adolescent social behavior and whole-brain cFos activation - Brown, Stephanie E.; Wang, Ziyi (Zephyr); Newman, Emily L.; Engin, Elif; Berretta, Sabina; Balu, Darrick T.; Folorunso, Oluwarotimi O. (Frontiers in Psychiatry, 2024)
Neurodevelopmental disorders (NDDs) can cause debilitating impairments in social cognition and aberrant functional connectivity in large-scale brain networks, leading to social isolation and diminished everyday functioning. To facilitate the treatment of social impairments, animal models of NDDs that link N-methyl-D-aspartate receptor (NMDAR) hypofunction to social deficits in adulthood have been used. However, understanding the etiology of social impairments in NDDs requires investigating social changes during sensitive windows during development. Here, we examine social behavior during adolescence using a translational mouse model of NMDAR hypofunction (SR-/-) caused by knocking out serine racemase (SR), the enzyme needed to make D-serine, a key NMDAR coagonist. In adolescent SR-/-mice, we observed disinhibited social behavior toward a novel conspecific and rapid social habituation toward familiar social partners. SR-/-mice also spent more time in the open arm of the elevated plus maze which classically points to an anxiolytic behavioral phenotype. These behavioral findings point to a generalized reduction in anxiety-like behavior in both social and non-social contexts in SR-/-mice; importantly, these findings were not associated with diminished working memory. Species-typical social interactions are maintained through brain-wide neural activation patterns; therefore, we employed whole-brain cFos activity mapping to examine network-level connectivity changes caused by SR deletion. Inter-regional patterns of cFos activation revealed greater connectivity and network density in SR-/-mice compared to controls. These results suggest that NMDAR hypofunctiona potential biomarker for NDDscan lead to generalized behavioral disinhibition in adolescence, potentially arising from disrupted communication between and within salience and default mode networks.